Abiotic and biotic sources influencing spring new particle formation in North East Greenland. (October 2018) - Dall´Osto, M.; Simo, R.; Harrison, Roy M.; Beddows, D.C.S.; Saiz-Lopez, A.; Lange, R.; Skov, H.; Nøjgaard, J.K.; Nielsen, I.E.; Massling, A.
Abstract: In order to improve our ability to predict cloud properties, radiative balance and climate, it is crucial to understand the mechanisms that trigger the formation of new particles and their growth to activation sizes. Using an array of real time aerosol measurements, we report a categorization of the aerosol population taken at Villum Research Station, Station Nord (VRS) in North Greenland during a period of 88 days (February–May 2015). A number of New Particle Formation (NPF) events were detected and are herein discussed. Air mass back trajectories analysis plotted over snow-sea ice satellite maps allowed us to correlate early spring (April) NPF events with air masses travelling mainly over snow on land and sea ice, whereas late spring (May) NPF events were associated with air masses that have passed mainly over sea ice regions. Concomitant aerosol mass spectrometry analysis suggests methanesulfonic acid (MSA) and molecular iodine (I2 ) may be involved in the NPF mechanisms. The source of MSA was attributed to open leads within the sea ice. By contrast, iodine was associated with air masses over snow on land and over sea ice, suggesting both abiotic and biotic sources. Measurements of nucleating particle composition as well as gas-phase species are needed to improve our understanding of the links between emissions, aerosols, cloud and climate in the Arctic; therefore our ability to model such processes. Highlights: New particle formation (NPF) events were detected at Villum Research Station, Station Nord (VRS) during spring 2015. NPF events indicates various sources (abiotic and biotic) of aerosol precursors in Arctic background conditions. Elevated concentrations of I2 and methanesulfonic acid (MSA) point to a diversity of precursors for aerosol production.